Media Informasi untuk Bank Baterai Berbasis Augmented Reality - Raymond Y. Purba; Suci Aulia; Agus Gunarso (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
Based on data from the pre-questionnaire related information media needs at PT. Telkom WITEL Bandung, 75% of employees have not known yet about battery bank information in detail and the rest of population only know from manual book and internet. The difficulty to get information from a device causes few actions and decisions that are not in accordance with standard procedures. On the other hand, manual book only give information concretely, making it difficult for employees to understand the information quickly and precisely which causes low reading interest. Implementation of Augmented Reality (AR) as a battery bank information media could be the best option of technology application that could deliver information digitally. In AR, users will get the experience that information appears directly like physical object so it would be more realistic, interactive, and easy to understand. In this study, a design of AR applications uses Luther Sutopo methodology based on Multimedia Development Life Cycle (MDLC) with AR Marker Based Tracking Type. The results of functional test show that the application is running properly and ready to be used as a battery bank information media system at PT. Telkom WITEL Bandung. This application can also be downloaded at Google Play Store.